O modular no vestuário masculino - Ferronato, Thais (2015)
The work aims to find solutions that allow greater usability garment to its users. Thus, research has been done to understand the relationship of man with his dress, his tastes and lifestyle. In addition to how the modularity and how it can be implemented in modeling in order to generate new possibilities. Not forgetting the needs met by this public regarding the comfort, quality and practicality, combined with aesthetics.